Evaluation of dietary α-lipoic acid supplementation on the growth performance and physiological status of striped catfish Pangasianodon hypophthalmus - Ratnawati Rifai; Dedi Jusadi; Muhammad Agus Suprayudi; Alimuddin; Sri Nuryati (Jurnal Akuakultur Indonesia, 2022)
This study aimed to evaluate the dietary supplementation of α-lipoic acid (ALA) on the growth performance, antioxidative capacity, and protein-sparring effect of striped catfish (Pangasianodon hypophthalmus) fingerling. The striped catfish (individual weight of 1.4 ± 0.0 g) were stocked in 25 cages at 2x1x1.5 m size in a 200-m pond at 50 fish. Fish were fed formulated diets with ALA supplementation, namely: diet A (27% protein: 390 kcal), diet B (27% protein: 390 kcal +ALA 8 g/kg), diet C (27% protein: 400 kcal), diet D (27% protein: 400 kcal +ALA 8 g/kg), and diet E (30% protein: 390 kcal). Feeding was performed until apparent satiation for 60 days. The ALA supplementation significantly produced higher final individual weight, specific growth rate, and protein efficiency ratio, followed by a lower feed conversion ratio on the 27:390+ALA diet treatment (P<0.05) than other diet treatments. The highest liver performance based on superoxide dismutase enzyme activity and glycogen contents was obtained from the 27:390+ALA diet treatment. The malondialdehyde, triglycerides, and lipid accumulation in the liver on the 27:390+ALA diet treatment were lower than other diet treatments (P<0.05). Therefore, the best growth performance and physiological status in striped catfish was obtained from 27:390+ALA diet treatment.